The role of norms in early stages of business relationships: An action research approach - Christoph M. Ott (jbm - Journal of Business Market Management, 2012)
Long-term business relationships between actors are a common mode of exchange in business markets. There has been increasing interest in the governance of long-term business relationships. However, little is known about governance issues in early stages of relationships. The goal of this paper is to put forth a seldom-used methodological approach in marketing to contribute to understanding the role of behavioral norms during the pre-contractual phase of a long-term business relationship. The background of this research project is the initial stages of two case studies of long-term business relationship between a school and investment partners prior to the contract signature with the intent of establishing a new school. Results of the occurrence of norms show that both parties first need to define the framework of their relationship before beginning joint value creation. Furthermore, a gradual increase of usage of norms seems to have a positive effect on a nascent business relationship.
urn:nbn:de:0114-jbm-v5i4.314
Keywords: 650; behavioral norms; norm dimension; action research; relational exchange theory; long-term business relationships